Environmental and biological factors affect desiccation tolerance of algae from two rivers (Thailand and New Zealand) with fluctuating flow - Elizabeth A. Bergey (2018)
Flow variation associated with hydropower production causes periodic exposure of zones along the banks of regulated rivers. These zones have reduced algal biomass and lower productivity. We investigated whether algal assemblages in regulated rivers differed in tolerance to aerial exposure because understanding such tolerance could be used to alter water releases to improve downstream productivity. In field experiments, we tested algal tolerance to aerial exposure in 3 assemblages: green filamentous and cyanobacterial assemblages in Thailand and a mixed (filamentous green + cyanobacteria) assemblage in New Zealand. Algae-bearing stones were exposed at night, during the day (in sun or shade, with or without simulated rain), or continuously, or were continuously submerged (with a handling control). Exposure reduced cyanobacterial chlorophyll a, and reduction was greater with day than with night exposure. Mixed algal assemblages showed a similar pattern in chlorophyll a, but ash-free dry mass (AFDM) did not change (bleached algae remained). In contrast, green filamentous algae survived better when exposed than when submerged, and when exposed during the day than at night. Snails consumed green filamentous algae, and submersion resulted in high grazing loss of filamentous algae but not cyanobacteria. Grazing pressure was presumably lower at night during water release. For cyanobacteria, shade and rain slightly increased chlorophyll a retention. For filamentous green algae, shade had no effect, and rain was beneficial in the shade but not the sun. Our experiments demonstrated an interaction among variable hydraulic conditions, activity of grazing snails, and availability of grazing-susceptible algae. A longer wet-dry cycle, daytime water release, and a shaded riparian zone reduced aerial exposure effects on algal assemblages, indicating that water releases can be regulated to improve productivity in the downstream exposed zone.